2022
DOI: 10.1002/ece3.8711
|View full text |Cite
|
Sign up to set email alerts
|

Little hope for the polyploid endemic Pyrenean Larkspur (Delphinium montanum): Evidences from population genomics and Ecological Niche Modeling

Abstract: Species endemic to restricted geographical ranges represent a particular conservation issue, be it for their heritage interest. In a context of global change, this is particularly the case for plants which belong to high‐mountain ecosystems and, because of their ecological requirements, are doomed to survive or disappear on their “sky islands”. The Pyrenean Larkspur (Delphinium montanum, Ranunculaceae) is endemic to the Eastern part of the Pyrenees (France and Spain). It is now only observable at a dozen of lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…On the genome size of Ranunculaceae , few related studies involving ten genera (i.e., Ranunculus , Eranthis , Helleborus , Hepatica , Thalictrum , Delphinium , Anemone , Ficaria , Adonis , and Trollius ), showed that the 2C-value of diploid taxa significantly ranged from 0.5 to 57.3 pg and from 14.8 to 89.2 pg for tetraploid taxa ( Zonneveld 2001 ; Mabuchi et al 2005 ; Cires et al 2009 ; Cires et al 2010 ; Zonneveld 2010 ; Soza et al 2013 ; Zonneveld 2015 ; Mitrenina et al 2020 ; Mitrenina et al 2021 ; Salvado et al 2022 ; Seidl et al 2022 ). According to Salvado et al’s (2022) report on the genome size of Delphinium , the tetraploid D. montanum had a 1C value of 10.32 pg. Here, the 2C-value of D. subg.…”
Section: Discussionmentioning
confidence: 99%
“…On the genome size of Ranunculaceae , few related studies involving ten genera (i.e., Ranunculus , Eranthis , Helleborus , Hepatica , Thalictrum , Delphinium , Anemone , Ficaria , Adonis , and Trollius ), showed that the 2C-value of diploid taxa significantly ranged from 0.5 to 57.3 pg and from 14.8 to 89.2 pg for tetraploid taxa ( Zonneveld 2001 ; Mabuchi et al 2005 ; Cires et al 2009 ; Cires et al 2010 ; Zonneveld 2010 ; Soza et al 2013 ; Zonneveld 2015 ; Mitrenina et al 2020 ; Mitrenina et al 2021 ; Salvado et al 2022 ; Seidl et al 2022 ). According to Salvado et al’s (2022) report on the genome size of Delphinium , the tetraploid D. montanum had a 1C value of 10.32 pg. Here, the 2C-value of D. subg.…”
Section: Discussionmentioning
confidence: 99%
“…We used an Ecological Niche Modelling (or Environmental Niche Modelling, ENM or Species Distribution Modelling, SDM) framework similar to the one we followed and described in detail in Salvado et al, (2022) to infer the spatio-temporal dynamics of suitable habitat for the O. aveyronensis species complex since the Last Glacial Maximum (LGM, 21 kyrs BP). We then compared the results with those obtained from population genomic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…This statement should be treated with skepticism because it is based only on one, empirical, study. Others who have used polyRAD to subset their datasets and identify diploid loci to use for population genomics [28,29], which is a practice aligned with assumptions of common methods [28], have not explored the use of all loci and/or tetraploid loci in comparison to only ones that segregate as diploids. It would be useful for additional studies on the population genomics of polyploid species to examine data employing all, diploid, and tetraploid (and higher) loci to determine if similar or divergent results are recovered.…”
Section: Subsetting Diploid and Tetraploid Locimentioning
confidence: 99%